Analysis of the Relationship Between Financial Failures and Sustainability Reports of Companies Publishing SASB Reports - Buse Öktem; Selahattin Karabınar (İstanbul İktisat Dergisi)
What the relationship is between a company’s sustainability report and its financial performance is a question awaiting an answer. One answer to this question involves determining the place and impact financial sustainability has with regard to overall sustainability. As such, this article analyzes the relationship between the concept of sustainability and the concept of financial failure based on whether companies with a high probability of financial failure published a sustainability report in the same period. As an indicator of financial failure, the Z’’ score developed by Altman and Hotchkiss (2006) for non-manufacturing and specific industries (retailers, telecommunications, airlines, etc.) was taken as the basis. The transportation sector was selected among the companies with published SASB reports because the transportation sector is one of the certain nonmanufacturing sectors for which the Z” score was developed. This sector shows 43 companies that have published SASB reports and financial data to be accessible for 40 companies. However, no Z’’ score has been calculated for companies founded since 2017, thus the Altman Z’’scores were calculated according to the five-year financial statements 39 companies had published between 2016-2020. The study examines whether companies with a Z’’ score under 4.35 (indicating financial difficulty) and companies with a Z’’ score between 4.35-5.85 (indicating the financial gray zone) have published sustainability reports. The results of the paper show the number of companies that published sustainability reports to have increased in recent years, even companies that are in trouble or financial uncertainty. In other words, eight companies were found to be in financial distress for the five years between 2016-2020, with four of these companies having published sustainability reports during that time, three being airline companies and one operating in the automobile sector.